REBUILDING COMPATITVNESS ATTRACTION OF GOLF TOURISM KOSAIDO COUNTRY CLUB IN SIGAR PENJALIN VILLAGE, TANJUNG DISTRICT, KAB. NORTH LOMBOK - Eka Aprianto; I Wayan Suteja; ulfan Mulyawan (Journal Of Responsible Tourism, 2023)
This study discusses the strategy of rebuilding the competitiveness of the Lombok Kosido Golf Country Club. which focuses on developing its tourist attraction. Tourism development is the main theory used in this research and data collection uses interview, observation and documentation techniques which are ultimately analyzed descriptively because the data analysis used is descriptive method. The results showed that the attraction found was the product which was divided into four packages. Includes 1 round 18 hole package which is a golf player package at a price of 1,775,000/pax (1 person), 1 round 9 hole package is a golf game package. The one priced at 1.650.000/pax (1 person), the 2 person package 1 round 18 holes is the golf game package at the price of 1.450.000/pax, the 2 person package 1 round 9 hole 1.150.000/pax. The facilities available at Lombok golf kosaido country club include 18-hole golf. APLAGI certificate, golf cart, golf club rental, shoe and umbrella rental, driving range, proshop, locker/toilet, prayer room, restaurant, parking lot. And the panoramas offered at the Kosaido Golf Country Club Lombok are Sire Beach and Medane Beach, Gili Tiga Islands (Trawangan, Meno and Air), Mount Rinjani, Lombok's wildlife. The strategies found and recommended are strangth-opportunities, including offering quality and well-known products at affordable prices, maximizing customer service, maximizing product sales through social media. As well as maintaining the company's image in the eyes of the public so as to increase customer loyalty.